1995
DOI: 10.1055/s-2007-1022800
|View full text |Cite
|
Sign up to set email alerts
|

Die spontane maligne Transformation einer extraabdominalen Fibromatose in ein Fibrosarkom

Abstract: The desmoid tumour with infiltrative and destructive growth tendencies, is a rare benign alteration of the connective tissue from musculo-aponeurotic structures and fascial sheaths. The exact pathogenesis is unknown, however trauma (surgery), genetic (Gardener's Syndrome) or hormonal factors (pregnancy) have been implicated. A spontaneous malignant transformation of a desmoid (extra-abdominal fibromatosis) to a fibrosarcoma is a rarity. Only one case is recorded in the literature. We report on the second case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Like extra-abdominal desmoid tumors, intrathoracic desmoid tumors demonstrate variable disease courses. Although there is a possibility of malignant transformation in extra-abdominal desmoid tumors, malignant formation in intrathoracic desmoid tumors has not yet been reported 4 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Like extra-abdominal desmoid tumors, intrathoracic desmoid tumors demonstrate variable disease courses. Although there is a possibility of malignant transformation in extra-abdominal desmoid tumors, malignant formation in intrathoracic desmoid tumors has not yet been reported 4 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The condition is benign, despite its aggressive and locally infiltrating growth pattern. Spontaneous malignant transformation of fibromatosis of the female breast to fibrosarcoma is possible, albeit rare [21]. Two such cases have been reported [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Desmoid fibroma is a rare, semimalignant lesion, representing 1.5±3.5 % of all connective tissue tumors [20]. It originates most frequently from the aponeurosis of the rectus abdominal muscle of multipara women.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have found postoperative irradiation necessary as well [7,8]. Malignant transformation of this lesion has been described in one case only [20].…”
Section: Introductionmentioning
confidence: 99%